Time-resolved CIDNP study of non-native states of bovine and human alpha-lactalbumins. - Morozova, O; Hore, P; Bychkova, V; Sagdeev, R; Yurkovskaya, A (2005)
The reaction mechanism and details of the formation of CIDNP (chemically induced dynamic nuclear polarization) in the photoreactions of the aromatic dye 2,2'-dipyridyl with non-native states of bovine and human alpha-lactalbumins (BLA and HLA) in aqueous solution have been studied using the time-resolved CIDNP technique. Non-native states have been obtained at pH 2 in the presence of 0, 8, and 10 M urea-d(4) and at pH 6.7 in the presence of 10 M urea-d(4). The dependence of the geminate CIDNP spectra of the two proteins on the denaturant concentration is shown to be determined by the intrinsic reactivity of the amino acid residues toward the triplet excited dye rather than by structural changes in the proteins. Values of the proton paramagnetic relaxation times (T(1)) have been obtained from an analysis of the CIDNP kinetics. For tryptophan and tyrosine residues, the T(1) values change in opposite directions when the proteins are progressively denatured, reflecting the different internal mobilities of the two types of residues. It has been found that for both BLA and HLA the CIDNP kinetics of the non-native states formed at pH 6.7 in the presence of 10 M urea are almost identical to those at pH 2 with no urea, suggesting that the polarizable amino acid side chains have closely similar solvent accessibilities and motional properties in the two non-native states.